2008
DOI: 10.1016/j.pain.2008.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of a long-term negative affective state following the induction of either acute or chronic pain

Abstract: Clinically, pain is a complex phenomenon consisting of both sensory and affective aberrations that can persist indefinitely. Pre-clinically, several animal paradigms have been established that reliably mimic both the acute and chronic aspects of pain pertinent to the human condition; however, the commonly used behavioral models only assess the sensory component of pain elicited by an evoked nociceptive stimulus. Since the affective-motivational component of pain is an important determinant of the overall pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 36 publications
6
51
0
Order By: Relevance
“…Furthermore, the study of Hummel et al has also shown how this pain-induced aversion is attenuated by a nonanalgesic, non-rewarding dose of morphine [35] . Thus, this paradigm is not only a useful methodology for modeling the sensory and affective components of pain, but also a novel strategy for gaining better insight into the pharmacology of pain-ameliorating therapies for treating pain-related affection.…”
Section: Paradigm Of Modified Cpa Coupled With Novel Objectsmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, the study of Hummel et al has also shown how this pain-induced aversion is attenuated by a nonanalgesic, non-rewarding dose of morphine [35] . Thus, this paradigm is not only a useful methodology for modeling the sensory and affective components of pain, but also a novel strategy for gaining better insight into the pharmacology of pain-ameliorating therapies for treating pain-related affection.…”
Section: Paradigm Of Modified Cpa Coupled With Novel Objectsmentioning
confidence: 94%
“…In this paradigm, rats subjected to inflammatory-and neuropathic-like pain show a prolonged negative association (for up to one month) with the pain-associated environment enriched with novel objects, after a number of conditioning sessions [35] .…”
Section: Paradigm Of Modified Cpa Coupled With Novel Objectsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many reasons to think that pain and mood have a reciprocal interaction. The affective-motivational component of pain is an important determinant of the overall pain experience, and negative affect may cause an increase in the manifestation and expression of pain-related disorders, both in humans (11) and in rodents (12). Although the primary drugs used for the management of chronic pain have traditionally been opioid receptor agonists and nonsteroidal antiinflammatory drugs, antidepressants (such as serotonin noradrenaline reuptake inhibitors and tricyclic antidepressants) are also used to treat chronic pain.…”
Section: Introductionmentioning
confidence: 99%